Disiplin Kerja, Beban Kerja dan Kinerja Karyawan Implikasinya pada Kinerja Organisasi - Yuliantini, Tine; Suryatiningsih, Suryatiningsih (Oikonomia: Jurnal Manajemen, 2021)
PurposeThis study aimed to identify and analyze the effect of work discipline and workload on employee performance and its implications for the organizational performance of PT ISS Indonesia at Mercu Buana University. MethodologyThe research method used in this research is causal research. The object of this research are 60 employees of PT ISS Indonesia at Mercu Buana University. The data analysis methods used in this research are SPSS and Partial Least Square (PLS). Findings The results showed that work discipline has a positive and significant effect on the employee performance. Workload has a positive and significant effect on the employee performance. Employee performance has a positive and significant effect on the organizational performance of PT ISS Indonesia at Mercu Buana. Suggestion Need to improve the balance between tasks or work and increase discipline in the implementation of work targets to increase efficiency in the implementation of tasks that will increase organizational performance by producing products efficiently.